2019
DOI: 10.3389/fchem.2018.00649
|View full text |Cite
|
Sign up to set email alerts
|

In situ Synthesis of Au-Induced Hierarchical Nanofibers/Nanoflakes Structured BiFeO3 Homojunction Photocatalyst With Enhanced Photocatalytic Activity

Abstract: In order to further improve the photocatalytic performance of BiFeO3 (BFO), novel Au-induced hierarchical nanofibers/nanoflakes structured BiFeO3 homojunctions (Aux-BFO, x = 0, 0. 6, 1.2, 1.8, 2.4 wt%) were in situ synthesized through a simple reduction method with assist of sodium citrate under the analogous hydrothermal environment. The effect of loading amount of Au nanoparticles (NPs) on the physicochemical properties and photocatalytic activity was investigated in detail. The Au1.2-BFO NFs sample show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…When the Au content further increases, the performance of the catalyst decreases due to the opacity and light scattering caused by excess Au NPs, which reduces the utilization of sunlight . In addition, excess Au NPs may in turn act as charge recombination centers, thereby inhibiting the effective utilization of charge carriers and leading to a decrease in photocatalytic efficiency . Meanwhile, the crushed double-shell hollow dodecahedrons demonstrated a significant reduction in performance (Figure S14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Au content further increases, the performance of the catalyst decreases due to the opacity and light scattering caused by excess Au NPs, which reduces the utilization of sunlight . In addition, excess Au NPs may in turn act as charge recombination centers, thereby inhibiting the effective utilization of charge carriers and leading to a decrease in photocatalytic efficiency . Meanwhile, the crushed double-shell hollow dodecahedrons demonstrated a significant reduction in performance (Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…42 These results further confirmed that the Au/N−In 46 In addition, excess Au NPs may in turn act as charge recombination centers, thereby inhibiting the effective utilization of charge carriers and leading to a decrease in photocatalytic efficiency. 47 Meanwhile, the crushed doubleshell hollow dodecahedrons demonstrated a significant reduction in performance (Figure S14). It indicates that the morphology has a certain influence on the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Data collection and data reduction were performed using Agilent's CrysAlisPro software (Yarnton, Oxfordshire, UK) [79]. Structure solution and refinement were performed with ShelX [80,81], and Olex2 was used for graphical representation of the data [82]. All molecular modeling calculations were performed using Gaussian 09 [83] using the WebMO interface.…”
Section: Methodsmentioning
confidence: 99%
“…Among the Au x -BFO structures, the Au 1.2 -BFO sample proved the best photocatalytic activity (85.76%) after 3h of irritation, being much higher than pristine BFO samples (49.49%) considering the same experimental conditions. The authors attributed the notorious improvement of photocatalytic activity primarily to the SPR effect of Au NPs in the hierarchical of Au-BFO nanostructured homojunction and secondly to the structural defects (Fe 2+ /Fe 3+ pairs and oxygen vacancy) [81].…”
Section: Sol-gel Methodsmentioning
confidence: 99%